Neptunium(VI) solubility in alkaline CaCl2 solutions: evidence for the formation of calcium neptunates CaxNpO3+x(s,hyd) - Fellhauer, David; Gaona, Xavier; Rothe, Jörg; Altmaier, Marcus; Fanghänel, Thomas (Monatshefte für Chemie, 2018)
The solubility behavior of hexavalent neptunium (Np) was systematically investigated as function of [CaCl2] = 0.25-4.5 mol dm−3 [0.252-5.26 mol (kg H2O)−1] and pHm 8-12 (pHm = − log{m(H+)/mol (kg H2O)−1}) under oxidizing conditions adjusted by hypochlorite. As solubility limiting Np(VI) solid phase, hitherto unknown, non-stoichiometric calcium neptunates, CaxNpO3+x(s,hyd), were identified by applying a wide range of analytical techniques including quantitative chemical analysis, powder XRD, Np L3-edge XANES, and SEM-EDX. The Ca:Np ratio in the equilibrium solid phase increased systematically with the pHm values in the batch solubility samples, and ranged between 0.60:1 and 1.66:1. For pHm > 10.5, the solubility of the calcium neptunates is around log{[Np]/mol (kg H2O)−1} ≈ − 6.1 ± 0.4 and does not show a strong dependence on [CaCl2]. For pHm < 10.5, log [Np] ranges from − 6.6 in 0.25 mol dm−3 CaCl2 to − 3.6 in 4.5 mol dm−3 CaCl2, and increases systematically with [CaCl2]. Based on the solubility data, the principle solid-liquid equilibrium reactions were qualitatively evaluated. The results for Np(VI) obtained in the present work were found to be different from the behavior of U(VI) in alkaline CaCl2 solutions, where the well-defined crystalline CaU2O7·3H2O(cr) phase controls the U(VI) solubility over a wide range of pHm and [CaCl2] conditions.